Transbronchial needle aspiration cytology of endobronchial abnormalities: does it increase the positivity rates of bronchoscopy (Journal of Pathology of Nepal, 2014)
Background: Negative results in bronchoscopic sampling techniques increase costs and delay treatment. We analyzed if addition of transbronchial needle aspiration (TBNA) increases the diagnostic yield of bronchoscopy. Materials and Methods: Patients with endobronchial abnormalities in whom a full set of sampling techniques (lavage, TBNA, biopsy and brushing) were done and had a confirmed diagnosis of lung cancer by one or more methods were included. The positivity rates of each of the sampling techniques and their various combinations were studied. We compared the positivity rates of bronchoscopy with and without TBNA. We also studied if TBNA was more valuable in any specific type, histology or position of endobronchial abnormalities. Results: The overall positivity rate of TBNA was 56%. It was higher than lavage and brushing but lower than biopsy. The addition of TBNA to the routine combination of sampling tachniques (lavage, biopsy and brushing) increased diagnostic yield from 76% to 86.6%. Contrary to previous reports, the increase in diagnostic yields did not differ significantly between types (exophytic vs submucosal), side or location of the endobronchial lesions. TBNA was found to have a significantly better positivity rates in small cell carcinoma than in non-small cell carcinoma cases. Conclusion: TBNA is a safe sampling technique for endobronchial abnormalities during bronchoscopy. It increases the diagnostic yields of bronchoscopy and this increase seems to be uniform amongst different types, histologies and locations of endobronchial abnormalities. DOI: http://dx.doi.org/10.3126/jpn.v4i7.10324 Journal of Pathology of Nepal (2014) Vol. 4, 565-569